A More Rapid Method for Culturing LUHMES-Derived Neurons Provides Greater Cell Numbers and Facilitates Studies of Multiple Viruses - Adam W. Whisnant; Stephanie E. Clark; José Alberto Aguilar-Briseño; Lorellin A. Durnell; Arnhild Grothey; Ann M. Miller; Steven M. Varga; Jeffery L. Meier; Charles Grose; Patrick L. Sinn; Jessica M. Tucker; Caroline C. Friedel; et al. (Viruses, 2025)
The ability to study mature neuronal cells ex vivo is complicated by their non-dividing nature and difficulty in obtaining large numbers of primary cells from organisms. Thus, numerous transformed progenitor models have been developed that can be routinely cultured, then scaled, and differentiated to mature neurons. In this paper, we present a new method for differentiating one such model, the Lund human mesencephalic (LUHMES) dopaminergic neurons. This method is two days faster than some established protocols, results in nearly five times greater numbers of mature neurons, and involves fewer handling steps that could introduce technical variability. Moreover, it overcomes the problem of cell aggregate formation that commonly impedes high-resolution imaging, cell dissociation, and downstream analysis. While recently established for herpes simplex virus type 1, we demonstrate that LUHMES neurons can facilitate studies of other herpesviruses, as well as RNA viruses associated with childhood encephalitis and hemorrhagic fever. This protocol provides an improvement in the generation of large-scale neuronal cultures, which may be readily applicable to other neuronal 2D cell culture models and provides a system for studying neurotrophic viruses. We named this method the Streamlined Protocol for Enhanced Expansion and Differentiation Yield, or SPEEDY, method.